تحضير ودراسة الخواص البلورية للمركبCa1-xSmx0.9Sr0.1FeO1.5 بطريقة محلول -هلام - لحسن, دواشي; محمد الصالح, موساوي (universty of elouedجامعة الوادي, 2020)
يرتكز هذا العمل على تحضير ودراسة الخواص البلورية لمركب البراونمليريت بواسطة إنعراج الأشعة السينية حيث تم تحضير عينات من مسحوق المركب 2.5 Ca(1-x) Sm (x) ]0.9 Sr0.1 Fe O] والمطعم بـ Sm في مواضع الكالسيوم بنسب مختلفة (x=0.05,0.10,0.25) بطريقة محلول- هلام. باستعمال البرنامج "Rex- Powder diffraction" المعتمد على طريقة "Rietveld" للتحسين، قد تم التوصل إلى أن المركب يتبلور في الزمرة الفضائية Pnma بالإضافة إلى تحديد الوسائط البلورية للعينات. هذه النتائج تم مقارنتها مع نتائج دراسة سابقة للعينة بدون تطعيم (X=0). كذلك تم توظيفها في البرنامج "BS-1.81a" لرسم البنية البورية، فتحصلنا على شكل خلية الوحدة الإصطلاحية للمركب المدروس، وجدنا أنها تتكون من تناوب مجسمات رباعية الأسطح FeO_4 وثمانية الأسطح FeO_6 وفق الإتجاه b. تتموضع هذه المجسمات داخل الشبكة بطريقة تسمح بظهور قنوات شاغرة سداسية الشكل وفق المحور a يحتمل نقلها لأيونات O^(-2). بعد مقارنة البنية لاحظنا أن التطعيم بـ Sm أدى إلى زيادة في حجم المجسمات ثمانية الأسطح ما نتج عنه تغير في شكل تلك القنوات ونتوقع أن يؤدي هذا إلى زيادة الناقلية الأيونية في المركب.This work is based on the preparation and study of the crystalline properties of a brown-millerite compound by X-Ray diffraction. Samples were prepared to get the powder of the [Ca(1-x) Sm (x)]0.9 Sr0.1 Fe O2.5 compound and dopped by Sm at the calcium sites with different proportions (x=0.05,0.10,0.25) using the sol-gel method. The refinement was performed using the "Rex- Powder diffraction" software based on the "Rietveld" meth-od. It was concluded that the compound crystalizes in the Pnma space group, in addition to determining the crystalline parameters of the samples. These results were compared with the results of a previous study of the undoped sample (X=0). Also we had employed the "BS-1.81a" program to draw the Crystal structure. We obtained the shape of the basic unit cell of the compound under study, their crystal structures consist of alternating of FeO_4 Tetrahedra and FeO_6 Octahedra according to the direction b, which are positioned in within the lattice such a way as to allow the appearance of vacant hexagonal channels on the a-axis, potentially transporting the O^(-2) ions. After comparing the structures, we noticed that the doping by Sm led to an increase in the size of the Octahedra structures, which resulted in a change in the shape of these channels, and we expected that this will lead to an increase of the ionic conductivity in the compound.
مذكرة تخرج ماستر فيزياء
Keywords: البروانمليريت، إنعراج الأشعة السينية، 2.5 Ca(1-x) Sm (x) ]0.9 Sr0.1 Fe O]، طريقة محلول- هلام، طريقة "Rietveld"، النقل الأيوني.; Brownmillerite, X-Ray Diffraction, [Ca(1-x) Sm (x)]0.9 Sr0.1 Fe O2.5, Rietveld method, Sol-gel method, Ionic conductivity.